2016
DOI: 10.1002/acn3.369
|View full text |Cite
|
Sign up to set email alerts
|

Genomics implicates adaptive and innate immunity in Alzheimer's and Parkinson's diseases

Abstract: ObjectivesWe assessed the current genetic evidence for the involvement of various cell types and tissue types in the etiology of neurodegenerative diseases, especially in relation to the neuroinflammatory hypothesis of neurodegenerative diseases.MethodsWe obtained large‐scale genome‐wide association study (GWAS) summary statistics from Parkinson's disease (PD), Alzheimer's disease (AD), and amyotrophic lateral sclerosis (ALS). We used multiple sclerosis (MS), an autoimmune disease of the central nervous system… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 51 publications
7
62
2
Order By: Relevance
“…Given that monocyte activation by lipopolysaccharide occurs through TLR4-MyD88 signalling these findings suggested that TLR4-mediated activation of microglia/astrocytes generated a cell state of key importance in the development of PD. This finding is consistent with previous reports highlighting the involvement of the immune system in sporadic PD [5, 17, 38, 51]. …”
Section: Resultssupporting
confidence: 94%
“…Given that monocyte activation by lipopolysaccharide occurs through TLR4-MyD88 signalling these findings suggested that TLR4-mediated activation of microglia/astrocytes generated a cell state of key importance in the development of PD. This finding is consistent with previous reports highlighting the involvement of the immune system in sporadic PD [5, 17, 38, 51]. …”
Section: Resultssupporting
confidence: 94%
“…Regions contributing to PD heritability were significantly enriched for acetylation of histone H3 at lysine 27 ( P = 0.001; Supplementary Table 1), a mark of active regulatory regions. PD heritability was also enriched for histone marks in central nervous system, adrenal, and pancreatic cell types (Supplementary Table 2), in agreement with a previous study 13 .…”
supporting
confidence: 91%
“…With these results in mind, it is tempting to speculate that PD presents genetically as more of a systemic disorder, with a bias to brain pathology, as opposed to a primary brain disorder. In support of this view, PD-associated risk variants have been found associated with monocytes and the innate immune system 13,40,41 , in addition to lymphocytes, mesendoderm, liver-and fat-cells 42 . Recent work has also demonstrated a causal relationship between BMI and PD 43 , which together with the repurposing of exenatide (a glucagon-like peptide-1 receptor agonist currently licensed for the treatment of type 2 diabetes) for the potential treatment of PD 44 , highlights the need to look beyond the brain and selective neuronal vulnerability.…”
Section: Discussionmentioning
confidence: 82%